Trouble at the core: BRAF(V600E) drives multiple modes of T-cell suppression in melanoma - Bradley, Sherille D. (Oncoimmunology, 2015)
Several studies have demonstrated that oncogenic BRAF((V600E)) promotes T-cell suppression in melanoma by upregulating the transcription of a multitude of immunomodulatory chemokine and cytokine genes. BRAF((V600E)) has now been shown to act even more directly to evade cytotoxic T-cell recognition, by driving rapid internalization of human leukocyte antigen (HLA) class I from the tumor-cell surface and its intracellular sequestration.